2020
DOI: 10.1109/access.2020.2993767
|View full text |Cite
|
Sign up to set email alerts
|

A Deep Learning Framework for Detection of Targets in Thermal Images to Improve Firefighting

Abstract: Intelligent detection and processing capabilities can be instrumental in improving the safety, efficiency, and successful completion of rescue missions conducted by firefighters in emergency first response settings. The objective of this research is to create an automated system that is capable of real-time, intelligent object detection and recognition and facilitates the improved situational awareness of firefighters during an emergency response. We have explored state-of-the-art machine/deep learning techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 27 publications
(29 reference statements)
0
13
0
Order By: Relevance
“…In the literature there are several studies that have design efficient schemes to enhance situational awareness [4,[25][26][27][28]. However, their limitations are that they: (i) implement only object detection or only object tracking processes, (ii) consider only UAV or only terrestrial assets, and (iii) employ only RGB or only thermal cameras.…”
Section: Approachmentioning
confidence: 99%
“…In the literature there are several studies that have design efficient schemes to enhance situational awareness [4,[25][26][27][28]. However, their limitations are that they: (i) implement only object detection or only object tracking processes, (ii) consider only UAV or only terrestrial assets, and (iii) employ only RGB or only thermal cameras.…”
Section: Approachmentioning
confidence: 99%
“…The DQN framework is built on top of a VGG-net-like framework [25] as a backbone and is shown in Figure 2. The backbone framework is used as a feature extractor that produces 4096-d features on a 224x224 infrared/thermal image.…”
Section: H Network Architecturementioning
confidence: 99%
“…Machine learning does however, perform well in rapid assessment and production of a decision given the current set of circumstances. In other research outside of the scope of this paper, [25], [31] have developed a machine learning based methodology that detects and tracks objects of interest such as doors, ladders, people and fire in the thermal imagery generated by firefighter's thermal cameras. Such information may be valuable to further improve the reinforcement learning algorithm's ability to understand aspects of the environment that may be used in navigation or escape.…”
Section: Movement Planning Through Deep Q Learning For Firefighting A...mentioning
confidence: 99%
“…Another study reported by Zhang et al (2019) used a group of neurons termed as a capsule or vector for replacing traditional neurons and achieved equivariance by successfully encoding spatial information and properties of an input image. Bhattarai and Martínez-Ramón (2020) identified and classified objects in real time from thermal cameras carried by firefighters. The detection accuracy reported by authors varied from 70 to 95%, which depends on the depth of the convolution network layer.…”
Section: Introductionmentioning
confidence: 99%